2019
DOI: 10.1002/asia.201801814
|View full text |Cite
|
Sign up to set email alerts
|

Cu2+‐Induced Structural Isomers: Effect of Foreign Metal Ions on the Structure and Properties of Silver Nanoclusters

Abstract: Metal ions have an important impact on the precise control of the synthesis and atomic structural arrangement of noble metal nanoclusters. In this work, the effect of metal ions on the isomer generation of metal nanoclusters is revealed for the first time. Compared with the previous Ag23 nanoclusters with two face‐centered cubic (fcc) unit cells twisting 27°, the Ag23 isomer had a higher symmetry structure with two fcc unit cells almost overlapping. In addition, the UV/Vis absorption spectrum of the isomer sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…In addition, Huang et al reported the structural isomer of 5e [Ag 23 (PET) 18 (PPh 3 ) 8 ] NC and revealed the influence of Cu 2+ ion on the structural isomer of Ag 23 NC through the oxidation–decomposition–recombination (ODR) process (Figure ). Compared to the reported Ag 23 NC ( Ag 23 -1 , from Jin’s group) with the two fcc unit cells twisting 27°, the Ag 23 -2 isomer had a higher-symmetry crystal structure with the two fcc unit cells nearly overlapping and was accompanied by significant changes in electronic structure …”
Section: Chemical Inducements-triggered Reactionsmentioning
confidence: 67%
See 4 more Smart Citations
“…In addition, Huang et al reported the structural isomer of 5e [Ag 23 (PET) 18 (PPh 3 ) 8 ] NC and revealed the influence of Cu 2+ ion on the structural isomer of Ag 23 NC through the oxidation–decomposition–recombination (ODR) process (Figure ). Compared to the reported Ag 23 NC ( Ag 23 -1 , from Jin’s group) with the two fcc unit cells twisting 27°, the Ag 23 -2 isomer had a higher-symmetry crystal structure with the two fcc unit cells nearly overlapping and was accompanied by significant changes in electronic structure …”
Section: Chemical Inducements-triggered Reactionsmentioning
confidence: 67%
“…Compared to the reported Ag 23 NC 305 (Ag 23 -1, from Jin's group) with the two fcc unit cells twisting 27°, the Ag 23 -2 isomer had a higher-symmetry crystal structure with the two fcc unit cells nearly overlapping and was accompanied by significant changes in electronic structure. 213 4.3.2. Transformation with Different Sizes.…”
Section: Transformation Between Structural Isomersmentioning
confidence: 99%
See 3 more Smart Citations